Analisis efesiensi pemasaran hasil budidaya ikan bandeng (Chanos chanos) di Desa Banga Kecamatan Mawasangka Kabupaten Buton Tengah - Yorli, Novita Indriani; Nurdiana A; Annaastasia, Nurhuda; Sriwulan, Desy; Sidiq, Azwar (Universitas Halu Oleo, 2024)
This study aims to determine how big the margin and efficiency on the marketing of milkfish commodities in Banga Village, Mawasangka District, Central Buton Regency. This research was conducted in January 2023, located in Banga Village, Mawasangka District, Central Buton Regency. Data were obtained through interviews, observation, recording of milkfish cultivators. Data analysis was performed using quantitative descriptive analysis, margins and efficiency. The results showed that marketing channels for milkfish in Banga Village, Buton Regency, consisted of three marketing channels. Marketing Channel I, milkfish were sailed from cultivators to consumers, while the marketing channel II,milkfish production were sailed from cultivators to traders and then it sailed to consumers. In addition, marketing channel III the farmer sailed the milkfish to collector and then from collectors the milkfish production were sailed to consumers. Marketing channel I didn’t have any marketing margin because the milkfish production were directly sailed to consumers and fishermen shared 100% of their milkfish product. Marketing channel II had a margin of IDR 5,000/kg, and the fishermen shared of milkfish product was 83%. In addition, marketing channel III had a margin of IDR 10,000/kg and the fishermen sharedof their milkfish product was 71%.This study concluded that marketing channels in I, II and III were still efficient because of the fishermen shared were more than 50%.